2002
DOI: 10.1103/physrevlett.89.257404
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dephasing of Surface Plasmon Excitation in Silver Nanoparticles: Influence of Particle Size, Shape, and Chemical Surrounding

Abstract: By combination of two special methods, i.e., persistent spectral hole burning and laser assisted nanoparticle preparation, the dephasing time T2 of surface plasmon excitation in silver nanoparticles was systematically investigated. A strong dependence of T2 on the plasmon energy is found which reflects the relevance of interband damping and makes necessary a precise control of the particle shape when measuring T2. The influence of the reduced dimension on the dephasing dynamics was observed as a decrease of T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(139 citation statements)
references
References 23 publications
8
129
0
2
Order By: Relevance
“…Such a behavior of Γ(R) (without oscillations) resembles qualitatively the measured one for the Ag nanoparticles. 21 Our result for the Na nanoparticles mainly agrees with a similar results obtained in Refs. 29,30.…”
Section: A Plasmon Linewidth In a General Casesupporting
confidence: 93%
See 2 more Smart Citations
“…Such a behavior of Γ(R) (without oscillations) resembles qualitatively the measured one for the Ag nanoparticles. 21 Our result for the Na nanoparticles mainly agrees with a similar results obtained in Refs. 29,30.…”
Section: A Plasmon Linewidth In a General Casesupporting
confidence: 93%
“…Our calculation of the plasmon resonance linewidth vs resonance energy qualitatively correlate with the its behavior measured for single Au nanospheres. 19 But a similar calculation for the Ag nanoparticles with account for the influence of the bulk dielectric properties of the NPs on the damping process 21 gives, on the contrary, the increase of Γ with the energy of a plasmon resonance. This may be due to the fact that the bulk damping exceeds the surface one for MNs with the great radii.…”
Section: Environment Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, because of these additional size-dependent damping processes, the dielectric constant of small NPs can no longer be described by the bulk metal values. Experimental studies on ensembles of metallic NPs revealed the existence of such effects (16,19). However, comparisons between theory and ensemble measurements are still a matter of debate, because the inhomogeneities in NP size, shape, and local environment experimentally blur the homogeneous width of the SPR.…”
Section: Single-metal Np Absorption Spectroscopymentioning
confidence: 99%
“…4 The relaxation times of the SP excitations are also ultrashort, in the 10 − 100 fs range. [5][6][7][8][9] Such nanolocalization and ultrafast kinetics make plasmonic nanostructures promising for various applications, especially for the ultrafast computations, data control and storage on the nanoscale.…”
Section: -3mentioning
confidence: 99%